Clinical and epidemiological profile of patients with pressure injuries: a comparative study between public and private hospitals (Research, Society and Development, 2021)
Pressure injury (LP) occurs when a tissue is compressed by a bone prominence in contact with a surface. Their presence may aggravate the patient's state of health, generating pain and systemic impairment. The high rates of incidence, prevalence, mortality and costs from this condition, represent a serious public health problem. This study aimed to know the clinical and epidemiological profile of patients who acquired the LP during the hospitalization period, comparing the characteristics between the public and private hospitals. This is an analytical, comparative study with a quantitative approach, carried out by analyzing medical records, of adult patients who acquired LP during hospitalization in public and private hospitals. The general clinical profile of patients who acquired pressure injury in the hospital setting was: 50% female and 50% male; elderly (62%); with short hospital stay